The household economic burden for acute coronary syndrome survivors in Australia. Issue 1 (December 2016) - Hyun, Karice; Essue, Beverley; Woodward, Mark; Jan, Stephen; Brieger, David; Chew, Derek; Nallaiah, Kellie; Howell, Tegwen; Briffa, Tom; Ranasinghe, Isuru; Astley, Carolyn; Redfern, Julie
Abstract Background Studies of chronic diseases are associated with a financial burden on households. We aimed to determine if survivors of acute coronary syndrome (ACS) experience household economic burden and to quantify any potential burden by examining level of economic hardship and factors associated with hardship. Methods Australian patients admitted to hospital with ACS during 2-week period in May 2012, enrolled in SNAPSHOT ACS audit and who were alive at 18 months after index admission were followed-up via telephone/paper survey. Regression models were used to explore factors related to out-of-pocket expenses and economic hardship. Results Of 1833 eligible patients at baseline, 180 died within 18 months, and 702 patients completed the survey. Mean out-of-pocket expenditure (n = 614) in Australian dollars was A258.06 (median: A126.50) per month. The average spending for medical services was A120.18 (SD: A310.35) and medications was A66.25 (SD: A80.78). In total, 350 (51 %) of patients reported experiencing economic hardship, 78 (12 %) were unable to pay for medical services and 81 (12 %) could not pay for medication. Younger age (18–59 vs ≥80 years (OR): 1.89), no private health insurance (OR: 2.04), pensioner concession card (OR: 1.80), residing in more disadvantaged area (group 1 vs 5 (OR): 1.77), history of CVD (OR: 1.47) and higher out-of-pocket expenses (group 4 vs 1 (OR): 4.57) were more likely to experience hardship. Conclusion Subgroups of ACS patients are experiencing considerable economic burden in Australia. These findings provide important considerations for future policy development in terms of the cost of recommended management for patients.